An Improved Fuzzy Logic System for Handoff Controller Design in Micro Cellular Mobile Network - Singh, Gurpreet; Kaur, Amanpreet (International Journal of Computer Sciences and Engineering, 2025)
Wireless and mobile networks are rapidly extending their capabilities. The continuation of an active call is the most important quality measurements in cellular systems. Handoff process provides such a facility for cellular system. Handoff is the mechanism which provides the service of transferring the ongoing call from one Base station (BT) to another when the mobile terminal (MT) crosses the coverage boundary of two networks in order to avoid call termination .Handoff controller takes decision by periodically checking the measurement criteria (parameters) for continuation of an Active Call .To address Better Handoff Controller, The Best Approach is to have more checking parameters (measurement criteria) into account for taking handoff decision .This Paper Represents the use of two more meaning full parameters along with the existing parameters using the fuzzy logic (ANFIS). With this Handoff Decision Improved and Problems such as more network load and interference are removed and Number of Handoffs are Reduced.